Measurement of Natural Radioactivity and Radioactive Contour Maps in Soil Samples in Two Provinces in Lao PDR - VOLACHACK, Nyphonh; LEUANGTAKOUN, Somsavath; XAYHEUNGSY, Sonexay; SONTHIKOUMMAN, Kaisone; THAVIXAY, Phaytoune (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The main objective of the research is to measure the natural Radioactivity and analyze the specific activities of natural 226Ra, 232Th and 40K in 137 surface soil samples from two provinces in the central part of Laos Khammuone and Savannaket Provinces. The result of the study revealed that natural 226Ra, 232Th and 40K were found in soil surface with the average value of 26.5 ± 3.76 Bq/kg for 226Ra, 35.2 ± 3.2 Bq/kg for 232Th and 247.9 ± 16 Bq/kg for 40K respectively. The measurement results were compared with United National Scientific Committee on the Effects of Atomic Radiation Sources and Risks of Ionizing Radiation, Report to the General Assembly with Annexes, United Nations, New York, 2000. Furthermore, radioactive contour maps of all specific activities of 226Ra, 232Th and 40K were created by using ArcGIS Version 10.